2003
DOI: 10.1136/jcp.56.7.528
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new chromogenic medium, Uriselect 4, for the isolation and identification of urinary tract pathogens

Abstract: Aims: To compare the performance of a new chromogenic medium, Uriselect 4, with cystine lactose electrolyte deficient (CLED) agar and an established chromogenic agar, CPS ID 2 medium, for detection of urinary tract pathogens. Methods: Using a semiquantitative culture method, 777 samples were inoculated on to the three test media in duplicate. All bacterial strains that yielded a potentially significant growth were observed for colony colour and identified using standard methods. Results: Of the 777 samples tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 10 publications
3
10
0
2
Order By: Relevance
“…This finding is in keeping with previous studies demonstrating the increased ability of chromogenic media to isolate mixed growth of uropathogens from urine specimens (23,25). This is further supported in our study by the isolation of P. mirabilis from one urine specimen in significant amounts with E. coli from chromogenic agar, while E. coli alone was isolated from conventional media.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is in keeping with previous studies demonstrating the increased ability of chromogenic media to isolate mixed growth of uropathogens from urine specimens (23,25). This is further supported in our study by the isolation of P. mirabilis from one urine specimen in significant amounts with E. coli from chromogenic agar, while E. coli alone was isolated from conventional media.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, in most retrospective studies standard urine cultures were screened for candiduria, which means that urine was cultured on MacConkey and blood agar only. Some laboratories culture urines on Uriselect agar, which is a chromogenic agar that allows the preliminary identification of predominantly bacterial uropathogens (195). Although these culture methods are certainly sufficient to identify bacteria, they may be significantly less sensitive to recover C. albicans and non-C. albicans species.…”
Section: Definition and Diagnosis Of Candiduriamentioning
confidence: 99%
“…(2003) compared three chromogenic agars with traditional CLED agar and found that all three detected significantly more mixed growths than CLED agar ( P < 0·01). Similary, Perry et al. (2003a) showed that, of 168 confirmed mixed cultures, only 78% were recognized as polymicrobial on CLED medium compared with 99% on Uriselect 4 and 97% on CPS ID2.…”
Section: Detection Of Urinary Tract Pathogensmentioning
confidence: 86%